Mathématiques

Question

bonjour vous pouvez m'aider a faire cette exercices ça aussi ​
bonjour vous pouvez m'aider a faire cette exercices ça aussi ​

2 Réponse

  • Réponse:

    A=17x

    B=impossible

    C=10x(-3)+11x(10)

    =21x+7

    D=(2x*8+2x*x+1*8+1*x)-(3x-1)(2x+1)

    =(16x+3x+8+1x)-(3x-1)(2x+1)

    =(20x+8)-(3x*2x+3x*1-1*2x-1*1)

    =(20x+8)-(6x+3x-2x-1)

    =(20x+8)-(7x-1)

    =13x+7

  • Réponse:

    A= 17x

    A= 17x B= 3a(x²-x+1)

    A= 17x B= 3a(x²-x+1)C= 9x(3x+7)

    A= 17x B= 3a(x²-x+1)C= 9x(3x+7)D= (2x+1)(-2x+9)

    Explications étape par étape:

    A= 5x +2x +10x

    A= 5x +2x +10xA= x( 5+2+10)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3a

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]C= 9x (x-3+10+2x)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]C= 9x (x-3+10+2x)C= 9x(3x +7)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]C= 9x (x-3+10+2x)C= 9x(3x +7)D= (2x+1) (8+x) - (3x-1)(2x+1)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]C= 9x (x-3+10+2x)C= 9x(3x +7)D= (2x+1) (8+x) - (3x-1)(2x+1)D= (2x+1) [(8+x) -(3x-1)]

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]C= 9x (x-3+10+2x)C= 9x(3x +7)D= (2x+1) (8+x) - (3x-1)(2x+1)D= (2x+1) [(8+x) -(3x-1)]D= (2x+1)(8+x-3x+1)

    A= 5x +2x +10xA= x( 5+2+10)A= x(17)B=3ax²- 3ax + 3aB= 3a( x²-x+1)C= 9x(x-3) + 9x( 10+2x)C= 9x [(x-3) +(10+2x)]C= 9x (x-3+10+2x)C= 9x(3x +7)D= (2x+1) (8+x) - (3x-1)(2x+1)D= (2x+1) [(8+x) -(3x-1)]D= (2x+1)(8+x-3x+1)D= (2x+1)(-2x+9)